Consensus on Shared Measures of Mobility and Cognition: From the Canadian Consortium on Neurodegeneration in Aging (CCNA). (21st June 2018) - Montero-Odasso, Manuel; Almeida, Quincy J; Bherer, Louis; Burhan, Amer M; Camicioli, Richard; Doyon, Julien; Fraser, Sarah; Muir-Hunter, Susan; Li, Karen Z H; Liu-Ambrose, Teresa; McIlroy, William; Middleton, Laura; et al.
Abstract: Background: A new paradigm is emerging in which mobility and cognitive impairments, previously studied, diagnosed, and managed separately in older adults, are in fact regulated by shared brain resources. Deterioration in these shared brain mechanisms by normal aging and neurodegeneration increases the risk of developing dementia, falls, and fractures. This new paradigm requires an integrated approach to measuring both domains. We aim to identify a complementary battery of existing tests of mobility and cognition in community-dwelling older adults that enable assessment of motor-cognitive interactions. Methods: Experts on mobility and cognition in aging participated in a semistructured consensus based on the Delphi process. After performing a scoping review to select candidate tests, multiple rounds of consultations provided structured feedback on tests that captured shared characteristics of mobility and cognition. These tests needed to be sensitive to changes in both mobility and cognition, applicable across research studies and clinics, sensitive to interventions, feasible to perform in older adults, been previously validated, and have minimal ceiling/floor effects. Results: From 17 tests appraised, 10 tests fulfilled prespecified criteria and were selected as part of the "Core-battery" of tests. The expert panel also recommended a "Minimum-battery" of tests that included gait speed, dual-task gait speed, the Montreal Cognitive Assessment and Trail Making Test A&B. Conclusions: A standardized assessment battery that captures shared characteristics of mobility and cognition seen in aging and neurodegeneration may increase comparability across research studies, detection of subtle or common reversible factors, and accelerate research progress in dementia, falls, and aging-related disabilities.